BILATERAL SEROUS RETINAL DETACHMENT AS OCULAR MANIFESTATION IN ACUTE LYMPHOBLASTIC LEUKEMIA: A CASE REPORT: Poster Presentation - Case Report - General practitioner - Anthea Casey; Dian Estu Yulia (Majalah Oftalmologi Indonesia, 2023)
Introduction : Acute lymphoblastic leukemia (ALL) is known to cause several ocular involvements. However, retinal detachment is a rare complication. This report aims to present unusual ocular manifestations in the form of bilateral serous retinal detachment in a pediatric patient. Case Illustration : An 11-year-old girl with a diagnosis of relapsed ALL and thrombocytopenia was referred to the Ophthalmology Department due to sudden blurred vision. The patient was undergoing chemotherapy on the third cycle due to the relapse. Visual acuity was 1/300 in both eyes. Fundus examination showed bilateral serous retinal detachment. No treatment in ophthalmology was given due to the unstable condition of this patient. Discussion : Up to 90% of all leukemia patients have fundus changes during the disease. The presence of unilateral or bilateral serous retinal detachment as a sign of choroidal infiltration may be one of the manifestations of acute leukemia, both as a primary sign and a relapse. Literature has shown that chemotherapy, radiation, and systemic prednisone would improve the visual acuity in these patients. However, in this case, when the patient is unstable and experiencing a series of complications, we decided that life-saving treatment comes first. Conclusion : The incidence of ocular involvements in ALL could be due to the treatment and the disease itself. Prompt recognition of disease led to early systemic treatment and restoration of visual function. The goal of sight-saving comes second after life-saving treatments.